2016
DOI: 10.4081/monaldi.2015.747
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial Watanabe Spigot in the treatment of bronchobiliary fistula

Abstract: Bronchobiliary fistula (BBF) is a rare condition in which an abnormal communication exists between the bile ducts and the bronchial tree. Malignancy is the most common etiology of BBF, although many others are possible. A 74-year-old male patient with an inoperable Klatskin tumor presented with a complaint of yellow-green sputum and cough; the patient underwent fiber-optic bronchoscopy based on a preliminary diagnosis of bronchobiliary fistula. Using fiber-optic rigid bronchoscopy, the laterobasal segment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…As an example, in our patient, three episodes of expectoration of pieces of the EWS occurred. Recently, three cases of BBF treated with an EWS have been reported, including two cases after hepatectomy and one case of inoperable Klatskin tumor ( 6 , 22 ). To our knowledge, this is the first successful case report of BBF following thermal ablation for a liver tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, in our patient, three episodes of expectoration of pieces of the EWS occurred. Recently, three cases of BBF treated with an EWS have been reported, including two cases after hepatectomy and one case of inoperable Klatskin tumor ( 6 , 22 ). To our knowledge, this is the first successful case report of BBF following thermal ablation for a liver tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the endobronchial Watanabe spigot (EWS), a silicone blocker, has been used under fiber-optic bronchoscopy for bronchial occlusion of BBFs and prolonged pulmonary air leaks (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Among surgical interventions, highly invasive procedures such as diaphragmoplasty, skin valvuloplasty, and lobectomy are considered 1,4,5) . Other techniques include percutaneous transhepatic biliary drainage, PTC, or bronchoscopy-guided embolization with coils or plugs, liquid sclerosing agents such as fibrin glue or cyanoacrylate, and EWS [6][7][8][9][10][11][12][13][14][15][16][17] . Among these, 9 reports of 10 cases of bronchobiliary fistulas managed with bronchoscopy-guided treatment have been published (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive treatments usually include ERBD, ENBD, sphincterotomy, and percutaneous drainage (PD). [ 6 , 25 ] Most patients with BBF can experience relief of their symptoms after biliary drainage. In 2002, Tran et al first reported endoscopic sphincterotomy and stent placement that led to a significant improvement in symptoms in the treatment of a bronchobiliary fistula secondary to RFA.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Direct bronchoscopy has been reported to be a new treatment method, but more clinical experience is still necessary. [ 25 ] In this case, the multiple disciplinary team suggested that minimally invasive treatment might be used as palliative treatment due to patient's the poor clinical condition with advanced malignant tumors, poor general condition, and inability to undergo surgery. ENBD might provide stronger evidence for further confirmation of the diagnosis of BBF and potential treatment.…”
Section: Discussionmentioning
confidence: 99%